Building Financial Resilience: Strategies for Thriving in the Face of Economic Crisis - Antoni, Antoni; Karlin, Karlin (Economics Studies and Banking Journal (DEMAND), 2024)
Financial resilience of individuals and communities is becoming increasingly important in facing global economic challenges. In this context, fiscal and monetary policies play a crucial role in building financial resilience. This study aims to conduct a systematic literature review on the role of fiscal and monetary policy in supporting financial resilience. Through analysis of various relevant articles, this research highlights the basic concepts of financial resilience, the role of fiscal and monetary policies, factors that influence policy effectiveness, as well as challenges and opportunities in implementing these policies. The results show that fiscal and monetary policies can significantly strengthen the financial resilience of individuals and communities. The implications of this research include the importance of coordination between institutions in designing effective policies as well as expanding the literature on factors that influence the implementation of fiscal and monetary policies.